Education in music: A critical approach to talent and music education - Ligia Ivette ASPRILLA (Ediciones Universidad de Salamanca, 2015)
The importance of music to life and retention in all cultures, allow conceived as a context for development and learning, rather than as a professional specialty. Both culture and training process as institutionalized education, converge in the music field, which suggests that it is possible to educate in music. From this discussion, the notion of talent becomes problematic and explores the whole concept of musical intelligence; different forms of assessment of musical potential are analyzed and finally a model of integration ranging from early childhood to graduate training aims to develop and articulate corporeality to various forms of symbolic, formal logical and creative thinking. The axes of the model is characterized by its breadth, flexibility and variability of ways you can express.